2022
DOI: 10.1111/ppc.13022
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the UNI‐PAHNP on physical activity and nutrition behaviors in overweight/obese university students in Turkey

Abstract: This study aimed to determine the effectiveness of a Pender's health promotion model-based Physical Activity and Healthy Nutrition Program for University Students (UNI-PAHNP) as a means for improving university students' nutrition and physical activity behaviors. Method: A total of 110 overweight and obese students were randomized into study and control groups.Findings: Students in the intervention group showed significant decreases in body mass index and waist circumference and significant increases in step c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Four of them examined exercise intervention [37][38][39][40] and the leftovers examined behavioral intervention. [41][42][43] All studies that examined health outcomes reported PA benefits, including improved cardiorespiratory fitness, body composition, lipid profile, mood, mental health, and sleep quality. Among 296 participants receiving supervised exercise intervention, only 1 participant reported tibial pain.…”
Section: Benefits Versus Risks Associated With Pamentioning
confidence: 99%
“…Four of them examined exercise intervention [37][38][39][40] and the leftovers examined behavioral intervention. [41][42][43] All studies that examined health outcomes reported PA benefits, including improved cardiorespiratory fitness, body composition, lipid profile, mood, mental health, and sleep quality. Among 296 participants receiving supervised exercise intervention, only 1 participant reported tibial pain.…”
Section: Benefits Versus Risks Associated With Pamentioning
confidence: 99%